Implementation of Pancasila Student Profile in Economic Learning at SMAIT Al-Huda Wonogiri - Yuniati, Atika Nur; Jatmika, Surya (Universitas Muhammadiyah Surakarta, 2025)
The implementation of the Pancasila Student Profile (PPP) in economic learning is an important part of realizing students with character and competitiveness. However, its implementation still faces challenges, especially during the initial transition period of the Independent Curriculum. This study aims to describe the implementation of the six dimensions of PPP in economic learning at SMAIT Al-Huda Wonogiri and identify the obstacles faced. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The resource persons for this research include a curriculum teacher, an economics teacher and three students. Data analysis used for data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the six dimensions of PPP have been integrated in economic learning, including through thematic recitation, cross-cultural discussions, group work, independent tasks, innovative projects, and real-case problem-solving. However, the main obstacle lies in the lack of clarity of teachers' initial understanding of the PPP integration scheme and the lack of concrete outputs due to the focus on soft skills, not the academic aspect. In addition, students also experience difficulties in building critical reasoning skills. It is recommended that schools strengthen teacher training, provide clear technical guidance for PPP implementation, and develop contextual learning strategies that support the strengthening of soft skills on an ongoing basis.